Structural Adjustment, Economic Performance, and Aid Dependency in Tanzania - Agrawal, Isha (IMF Working Papers; Working Paper ;, 1993)
Tanzania's adjustment program, which began in the mid-1980s, was accompanied by a sharp increase in the levels of foreign assistance. Previous studies, using published data, have not reflected much improvement in economic performance during the reform period. This paper attempts to shed new light on the relationship between adjustment and aid dependency in Tanzania, by adjusting the macroeconomic database to correct for data deficiencies in several important respects. A subsequent comparison with other sub-Saharan African countries shows that, contrary to traditional interpretation, Tanzania's increased dependence on foreign assistance did not lead to a deterioration in domestic savings performance. Efficiency of investment, however, has been substantially lower in Tanzania.